Features of Epidemic Process of Tuberculosis in the Territory with High Prevalence of HIV Infection - S. N. Shugaeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Scales of epidemic process of HIV-associated of tuberculosis are especially noticeable in regions with high prevalence of HIV infection and tuberculosis. A striking example of this situation is the Irkutsk region – the territory with the highest prevalence of HIV infection in the Russian Federation and one of the most unsuccessful one on tuberculosis – in 2010 became Russian “leader” and in prevalence of the HIV-associated tuberculosis, keeping a position “in the first five” so far. It is clear, that all this cannot but imply negative manifestations of two considered epidemic processes at their simultaneous development in one territory. The above-said facts predetermined carrying out the retrospective epidemiological analysis of spread of tuberculosis among the cumulative population in the Irkutsk region, a territory of high risk of HIV infection.The purpose of the work was to assess features of spread of tuberculosis in the territory of the large center of HIV infection (Irkutsk region).Results. The expressed negative impact of HIV infection on epidemic process of tuberculosis in the studied region, shown in divergence of trends and higher levels of epidemiological indicators in comparison to the all-Russian data is established.Conclusion. As a result of a research the trend of regional incidence of tuberculosis, multidirectional with the all-Russian indicators, is established from the moment of epidemic spread of HIV infection that demonstrates integration of epidemic processes of the studied infections. Even on condition of regress of epidemic process of tuberculosis at the end of the analyzed period which is followed by decrease in incidence of all population, HIV infection has a significant impact on his tension that, certainly, demands the strengthened measures of epidemiological control of these socially important infections.